Explaining Ethnicity: Primordialism vs. Instrumentalism - Kataria, Shyamal (Advances in Social Sciences Research Journal, 2018)
Ethnicity, very much like gender, has long been viewed an inescapable facet of our social reality. All humans have an ethnicity, or at least are ascribed one throughout of lives. As such, there is a huge amount of scholarly intrigue attached to ethnicity from across both the biological and social sciences. In this respect, much of the focus has been on explaining how and why ethnicities form and persist through time. Two principal schools of thought on ethnicity are primordialism and instrumentalism. This article aims to impartially review and, where possible, scrutinise both perspectives in an attempt to arrive at a more precise and considered understanding of ethnicity.